The effect of peroperative erythrocyte transfusion on infectious complications in patients with gastric cancer undergoing curative gastrectomy - Ergin, Ahmet Sencer; Erşen, Ogün; Mercan, Ümit; Yüksel, Cemil; Demirci, Salim (International Surgery Journal, 2021)
Background: In this study, the effect of perioperative blood transfusion on infectious complications in patients undergoing curative surgery for gastric adenocarcinoma was investigated. Methods: The clinicopathological results of 312 patients who underwent curative gastrectomy were retrospectively analyzed. The effect of blood transfusion on the development of postoperative infectious complications were statistically analyzed. Results: In the subgroup of patients with intraoperative transfusion, surgical site infection incidence was found to be significantly higher in patient with 2U above ES transfusions. (p=0.014). In the subgroup of patients with postoperative transfusion, hospital stay (p<0.001), postoperative CRP values (p<0.001), surgical site infection incidence (p=0.049) and anastomosis leakage incidence (p<0.001) were found to be significantly higher in patient with 2U above ES transfusions. In the subgroup of patients with both intraoperative and postoperative transfusion, SSI, anastomotic leakage and any infective complication incidences were found to be significantly higher in patients with 2U and above transfusions. In multivariate analysis, age (p=0.015), BMI (p=0.011), intraoperative transfusion (p=0.011) and both intraoperative and postoperative transfusion (p=0.045) were found to be independent risk factors for infective complications. Conclusions: It was found that performing peroperative ES transfusion is associated with increased rates of infectious complications in patients undergoing curative gastrectomy for gastric cancer by causing immunomodulation.